Forming the First Concepts of Horse Word Group in Grades 1-2 Through Innovative Methods - Ne’matova Shahnoza Axmadjanovna (Zien Journals, 2022)
It is known that innovation embodies the essence of the process and activity of implementation of this renewal, change in practice.With their help it will be possible to develop and introduce innovative methods and technologies in the training of future primary school teachers. Innovation has been changing since the emergence of society. Some educators are replacing the word innovation in the narrow sense with improving, modernizing, perfecting, optimizing, and so on. The use of interactive methods in the educational process is an innovative way to increase the effectiveness of education
Keywords: effectiveness; innovation; embodies; technologies